Persepsi Masyarakat tentang Judi Online pada Era Digitalisasi di Kelurahan Harjosari II Medan Amplas - Dea Adinda; Erni Asneli Asbi (LPPM UNISDA, 2026)
Advances in digital technology have made it easier to access various internet-based activities, including online gambling, which is becoming increasingly prevalent in society and giving rise to various social, economic, and psychological impacts. This study aims to examine public perceptions of online gambling in the digital age in Harjosari II, Medan Amplas, focusing on the public's cognitive, affective, and psychomotor perceptions. The study employs a descriptive qualitative method with data collected through interviews, observation, and documentation involving seven informants. The findings indicate that, in cognitive terms, the public generally possesses knowledge of the forms, risks, and impacts of online gambling and views it as harmful behavior. In affective terms, the majority exhibit rejection, concern, and anxiety because online gambling is considered contrary to social and religious norms. In psychomotor terms, individuals who have been involved report negative impacts, while those not exposed tend to adopt preventive behaviors. The findings show that public perceptions of online gambling tend to be negative and view it as a social problem requiring prevention. It is therefore recommended that digital literacy be strengthened, parental supervision enhanced, the roles of community and religious leaders optimized, and cooperation between government and the public fostered.